Variabel-Variabel yang Mempengaruhi Keputusan Konsumen Menginap Di University Inn Umm - M Mursidi (Jurnal Teknik Industri, 2010)
This Research aim to wish to know influence of location, condition of physical ( Tangible Product) and service, security, freshment ( Intangible Product) to behavior of consumer in visit [in] University Inn UMM. Pursuant to result of research can be concluded that result of analysis span scale explain opinion of responder about various variable related to University Inn UMM which concerning Location, Condition of physical, Service, Security and Freshment very good. Result of analysis of regresi conclude that to five variable that is Location, Condition of physical, Service, Security and Freshment have an effect on to variable tied that is decision of konsumen. Pursuant to Test of F, please conclude that by simultan X variable have an effect on signifikan to variable Y. While conclusion of test of T that is test by parsial show X2 variable, X3, X4 have an effect on 5iglillikall to Y variable and of Xi, X2 have an effect on [do] not signifikan to variable Y. While most having an effect on variable, result of analysis of regresi indicate that value of coefisien regresi of variable of X3 ( biggest pelayanan) that is 0, 302 ( 30 %). This matter indicate that variable of X3 ( pelayanan) [is] most influencing variable [of] decision of consumer to lodge / [do] not [in] hotel of University Inn UMM. Pursuant to result of this research [of] researcher give suggestion for example to increase sale of hotei, need intensively marketing activity by extending marketing area and also string up cooperation network [pass/through] various government agency and of suasta and also or bureau of travel wisata from various area.